High-Throughput Multiple Dies-to-Wafer Bonding Technology and III/V-on-Si Hybrid Lasers for Heterogeneous Integration of Optoelectronic Integrated Circuits - Luo, Xianshu; Cao, Yulian; Song, Junfeng; Hu, Xiaonan; Cheng, Yuanbing; Li, Chengming; Liu, Chongyang; Liow, Tsung-Yang; Yu, Mingbin; Wang, Hong; Wang, Qi Jie; Lo, Patrick Guo-Qiang (Frontiers in Materials, 2015)
Integrated optical light source on silicon is one of the key building blocks for optical interconnect technology. Great research efforts have been devoting worldwide to explore various approaches to integrate optical light source onto the silicon substrate. The achievements so far include the successful demonstration of III/V-on-Si hybrid lasers through III/V-gain material to silicon wafer bonding technology. However, for potential large-scale integration, leveraging on mature silicon complementary metal oxide semiconductor (CMOS) fabrication technology and infrastructure, more effective bonding scheme with high bonding yield is in great demand considering manufacturing needs. In this paper, we propose and demonstrate a high-throughput multiple dies-to-wafer (D2W) bonding technology which is then applied for the demonstration of hybrid silicon lasers. By temporarily bonding III/V dies to a handle silicon wafer for simultaneous batch processing, it is expected to bond unlimited III/V dies to silicon device wafer with high yield. As proof-of-concept, more than 100 III/V dies bonding to 200 mm silicon wafer is demonstrated. The high performance of the bonding interface is examined with various characterization techniques. Repeatable demonstrations of 16-III/V-die bonding to pre-patterned 200 mm silicon wafers have been performed for various hybrid silicon lasers, in which device library including Fabry-Perot (FP) laser, lateral-coupled distributed feedback (LC-DFB) laser with side wall grating, and mode-locked laser (MLL). From these results, the presented multiple D2W bonding technology can be a key enabler towards the large-scale heterogeneous integration of optoelectronic integrated circuits (H-OEIC).